2004
DOI: 10.1111/j.1460-9568.2004.03511.x
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of N‐methyl‐d‐aspartate receptors, AMPA receptors or metabotropic glutamate receptors leads to rapid internalization of AMPA receptors in cultured nucleus accumbens neurons

Abstract: In hippocampus and other regions, alpha-amino-3-hydroxy-5-methylisoxazole-4-propionate (AMPA) receptors are inserted into synapses during long-term potentiation and removed during long-term depression. However, little is known about regulation of AMPA receptor trafficking in the nucleus accumbens (NAc), despite growing evidence that glutamate-dependent forms of plasticity in the NAc contribute to drug addiction. Using postnatal rat NAc cultures and an immunocytochemical method that selectively detects newly in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
31
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 60 publications
(185 reference statements)
3
31
0
Order By: Relevance
“…Calcium-dependent electrical activity in Xenopus spinal neurons homeostatically regulates specification of acetylcholine (ACh), glutamate, GABA, and glycine at early stages of development (1), depolarization increases the proportion of dopaminergic neurons in nodose, petrosal, and dorsal root rat ganglia (2), and specification of GABAergic and glutamatergic phenotypes in developing hippocampal rat granule cells depends on electrical activity (3). NMDA receptor (NMDAR) expression is modulated by early activity in the rat superior colliculus (4) and in cat and ferret visual cortex (5), and ␣-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid receptor (AMPAR) levels are activity-dependent in postnatal rat nucleus accumbens neurons (6). Kainate receptor expression depends on activity in postnatal rat thalamocortical synapses (7).…”
mentioning
confidence: 99%
“…Calcium-dependent electrical activity in Xenopus spinal neurons homeostatically regulates specification of acetylcholine (ACh), glutamate, GABA, and glycine at early stages of development (1), depolarization increases the proportion of dopaminergic neurons in nodose, petrosal, and dorsal root rat ganglia (2), and specification of GABAergic and glutamatergic phenotypes in developing hippocampal rat granule cells depends on electrical activity (3). NMDA receptor (NMDAR) expression is modulated by early activity in the rat superior colliculus (4) and in cat and ferret visual cortex (5), and ␣-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid receptor (AMPAR) levels are activity-dependent in postnatal rat nucleus accumbens neurons (6). Kainate receptor expression depends on activity in postnatal rat thalamocortical synapses (7).…”
mentioning
confidence: 99%
“…Although not described as of yet, alterations in protein associations within this complex could serve to prevent PKA access to GluR1. Other reports have demonstrated that glutamatergic activity via both AMPAR and NMDAR regulates trafficking of GluR1-containing AMPARs (Carroll et al, 1999;Beattie et al, 2000;Ehlers, 2000;Mangiavacchi and Wolf, 2004), and movement of GluR1 to distinct subcellular compartments could also potentially serve to uncouple PKA from GluR1. However, NMDAR-mediated endocytosis of GluR1 is a Ca 2ϩ -and phosphatase-dependent event.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the effect of the more selective Ro 25-6981 on the acquisition of conditioned fear or synaptic plasticity in the amygdala is currently unknown. In addition, AMPA receptor endocytosis occurs downstream of NMDA receptor activation in the induction of LTD (Ahmadian et al, 2004;Mangiavacchi and Wolf, 2004;Moult et al, 2006). Accordingly, activation of NMDA NR2B receptors would be expected to affect a number of different cellular processes, in addition to mediating AMPA receptor endocytosis.…”
Section: Ampa Receptor Endocytosis Does Not Mediate the Acquisition Omentioning
confidence: 99%